Proceedings of the 2001 ACM/IEEE Conference on Supercomputing 2001
DOI: 10.1145/582034.582037
|View full text |Cite
|
Sign up to set email alerts
|

Efficient network and I/O throttling for fine-grain cycle stealing

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…At the same time, we would like to maintain the average turnaround time and the quality of service of the primary jobs. Condor [4], LSF [5], NOW [6], and Linger-Longer [1,2,3,7] all present ways to exploit the available idle time in a network of nondedicated workstations while taking steps to limit the impact on the owner of the workstation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, we would like to maintain the average turnaround time and the quality of service of the primary jobs. Condor [4], LSF [5], NOW [6], and Linger-Longer [1,2,3,7] all present ways to exploit the available idle time in a network of nondedicated workstations while taking steps to limit the impact on the owner of the workstation.…”
Section: Related Workmentioning
confidence: 99%
“…In [2] and [3], the efficiency with which idle cycles were used by guest jobs as well as the change in the throughput of guest jobs was evaluated using simulation. In [7], the impact of I/O and network resources is considered, which is beyond the scope of the present work.…”
Section: Related Workmentioning
confidence: 99%
“…With several micro benchmarks, we demonstrated that I/O and network bandwidth usage of guest jobs could be limited effectively to within a few percent of target usages [10].…”
Section: I/o and Network Throttlingmentioning
confidence: 99%
“…However, the host job will be adversely affected unless the guest job's resource use is strictly limited. In this section, we summarize our earlier work [10,14] on resource policing mechanisms for CPU, memory, I/O and Network bandwidth.…”
Section: Resource Policingmentioning
confidence: 99%
See 1 more Smart Citation